2005
DOI: 10.1242/dev.01579
|View full text |Cite
|
Sign up to set email alerts
|

Insights into developmental mechanisms and cancers in the mammalian intestine derived from serial analysis of gene expression and study of the hepatoma-derived growth factor (HDGF)

Abstract: The vertebrate intestine is a model for investigating inductive cellular interactions and the roles of epithelial stem cells in tissue regeneration,and for understanding parallels between development and cancer. We have used serial analysis of gene expression to measure transcript levels across stages in mouse intestine development. The data(http://genome.dfci.harvard.edu/GutSAGE)identify novel differentiation products, potential effectors of epithelial-mesenchymal interactions, and candidate markers and regul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
70
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 63 publications
5
70
0
Order By: Relevance
“…This staining clearly overlaps with the domains of expression of Gata5 at similar developmental stages (Weber et al, 2000). Hepatoma derived growth factor [(HDGF); Clone 7C5] (Lepourcelet et al, 2005) showed a weak expression in endodermal cells during gastrulation (Fig. 2B), whereas Xenopus TGIF2 [(xTGIF2); clone 8B1] expression was enriched in dorsal and ventral/anterior endodermal cells at gastrula and neurula stages, respectively ( Fig.…”
Section: Identification Of Gata5 Transcriptional Targets Regulated Inmentioning
confidence: 99%
“…This staining clearly overlaps with the domains of expression of Gata5 at similar developmental stages (Weber et al, 2000). Hepatoma derived growth factor [(HDGF); Clone 7C5] (Lepourcelet et al, 2005) showed a weak expression in endodermal cells during gastrulation (Fig. 2B), whereas Xenopus TGIF2 [(xTGIF2); clone 8B1] expression was enriched in dorsal and ventral/anterior endodermal cells at gastrula and neurula stages, respectively ( Fig.…”
Section: Identification Of Gata5 Transcriptional Targets Regulated Inmentioning
confidence: 99%
“…71 HMGB1-RAGE interaction induces proliferation, angiogenesis, invasion, metastasis and chemotherapy-resistance. 71 Similarly, HDGF is overexpressed in many different cancers, including gastrointestinal stromal tumors (GISTs), 72 esophageal carcinoma, 73 pancreatic cancer, 74 hepatocellular carcinoma, 75 non-small cell lung cancer, 76 colorectal cancer 77 and melanoma, 78 and has potent angiogenic, 79 invasive 80 and metastatic potential. 73 Contrasting its role under pathophysiological conditions, such as gliomagenesis, necrosis can also be beneficial for an organism as it constitutes a warning system against toxic exposure.…”
Section: The Two Faces Of Necrosis-a Benefical Adaptive Warning Systementioning
confidence: 99%
“…Meanwhile, villus cells are postmitotic and express genes appropriate to their differentiated function in secretion or absorption; epithelial cells transit towards the villus tips, where they ultimately delaminate into the lumen. A number of developmental signaling molecules and transcriptional regulators have been implicated in villus development (Choi et al, 2006;Kaestner et al, 1997;Karlsson et al, 2000;Kim et al, 2007;Lepourcelet et al, 2005;Madison et al, 2005;McLin et al, 2009;Ormestad et al, 2006;Shyer et al, 2013;Spence et al, 2011;van den Brink, 2007;Walker et al, 2014;Walton et al, 2012Walton et al, , 2016; however, the role of metabolic regulators in villus development has yet to be investigated.…”
Section: Introductionmentioning
confidence: 99%